Autoantibody Landscape Revealed by Wet Protein Array: Sum of Autoantibody Levels Reflects Disease Status - Matsuda, Kazuki M.; Yoshizaki, Ayumi; Yamaguchi, Kei; Fukuda, Eriko; Okumura, Taishi; Ogawa, Koji; Ono, Chihiro; Norimatsu, Yuta; Kotani, Hirohito; Hisamoto, Teruyoshi; Kawanabe, Ruriko; Kuzumi, Ai; et al. (Frontiers in Immunology, 2022)
Autoantibodies are found in various pathological conditions such as autoimmune diseases, infectious diseases, and malignant tumors. However their clinical implications have not yet been fully elucidated. Herein, we conducted proteome-wide autoantibody screening and quantification with wet protein arrays consisting of proteins synthesized from proteome-wide human cDNA library (HuPEX) maintaining their three-dimensional structure. A total of 565 autoantibodies were identified from the sera of three representative inflammatory disorders (systemic sclerosis, psoriasis, and arteritis). Each autoantibody level either positively or negatively correlated with serum levels of C-reactive protein, the best-recognized indicator of inflammation. In particular, we discovered total levels of a subset of autoantibodies correlates with the severity of clinical symptoms. From the sera of malignant melanoma, 488 autoantibodies were detected. Notably, patients with metastases had increased overall autoantibody production compared to those with tumors limiting to the primary site. Collectively, proteome-wide screening of autoantibodies using the in vitro proteome can reveal the "autoantibody landscape" of human subjects and may provide novel clinical biomarkers.